Implementasi Keteladanan Yesus sebagai Guru Agung dalam Proses Pembelajaran Pendidikan Agama Kristen Kelas V SDN 38 Pahauman - Operahmat Halawa; Intan Deta Amelia (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to examine the implementation of Jesus' exemplary role as a Great Teacher in the Christian Religious Education learning process in fifth grade at SDN 38 Pahauman. Jesus is seen as a teacher who not only conveys knowledge but also instills noble spiritual values, character, and integrity in His students. Jesus' exemplary role, such as compassion, patience, firmness, humility, and the ability to teach teachings with real life, is an inspiration in the world of education, especially in Christian religious learning. This study uses a qualitative descriptive approach, with data collection techniques through observation of the learning process, interviews with Christian Religious Education teachers and students, and documentation of learning activities. The results of the study show that teachers strive to apply Jesus' exemplary role in every aspect of learning, both verbally and nonverbally. For example, teachers demonstrate compassion and patience in dealing with students who have different backgrounds and characteristics. Teachers also instill the values of firmness in enforcing discipline and use a contextual teaching approach, so that the teaching material can be more easily understood and applied by students in their daily lives. However, the implementation of Jesus' exemplary values still faces challenges, particularly in terms of consistent teacher behavior and a lack of support from the overall school environment. Several factors, such as limited time, teacher administrative burdens, and a lack of continuing education, also hinder the deep internalization of Christian values. The implications of these findings are the importance of training and strengthening the capacity of spiritual teachers so they can continue to be true role models for students. Furthermore, creativity is needed in integrating Gospel values into the learning process to shape students' overall character in accordance with Christ's example.